MR Measures of Small Bowel Wall T2 Are Associated With Increased Permeability. Issue 5 (16th December 2020) - Scott, Robert A.; Williams, Hannah G.; Hoad, Caroline L.; Alyami, Ali; Ortori, Catherine A.; Grove, Jane I.; Marciani, Luca; Moran, Gordon W.; Spiller, Robin C.; Menys, Alex; Aithal, Guruprasad P.; Gowland, Penny A.
Abstract : Background: Increased small bowel permeability leads to bacterial translocation, associated with significant morbidity and mortality. Biomarkers are needed to evaluate these changes in vivo, stratify an individual's risk, and evaluate the efficacy of interventions. MRI is an established biomarker of small bowel inflammation. Purpose: To characterize changes in the small bowel with quantitative MRI measures associated with increased permeability induced by indomethacin. Study Type: Prospective single‐center, double‐blind, two‐way crossover provocation study. Subjects: A provocation cohort (22 healthy volunteers) and intrasubject reproducibility cohort (8 healthy volunteers). Field Strength/Sequence: 2D balanced turbo field echo sequences to measure small bowel wall thickness, T2, and motility acquired at 3T. Assessment: Participants were randomized to receive indomethacin or placebo prior to assessment. After a minimum 2‐week washout, measures were repeated with the alternative allocation. MR measures (wall thickness, T2, motility) at each study visit were compared to the reference standard 2‐hour lactulose/mannitol urinary excretion ratio (LMR) test performed by a lab technician. All analyses were performed blind. Statistical Tests: Normality was tested (Shapiro–Wilk's test). Paired testing (Student's t ‐test or Wilcoxon) determined the significance of paired differences with indomethacin provocation. Pearson's correlation coefficient compared significant measures with indomethacin provocation to LMR. Intrasubject (intraclass correlation) and interrater variability (Bland–Altman) were assessed. Results: Indomethacin provocation induced a significant increase in LMR compared to placebo ( P < 0.05) and a significant increase in small bowel T2 (0.12 seconds compared to placebo 0.07 seconds, P < 0.05). Small bowel wall thickness ( P = 0.17) and motility ( P = 0.149) showed no significant change. T2 and LMR were positively correlated ( r = 0.68, P < 0.05). T2 measurements were robust to interobserver (intraclass correlation 0.89) and intrasubject variability (Bland–Altman bias of 0.005 seconds, 95% confidence interval [CI] –0.04 to +0.05 seconds, and 0.0006 seconds, 95% CI –0.05 to +0.06 seconds). Data Conclusion: MR measures of small bowel wall T2 were significantly increased following indomethacin provocation and correlated with 2‐hour LMR test results. Level of Evidence: 1 Technical Efficacy Stage: 2